Aplikasi Tourism Guide Provinsi Bengkulu Berbasis Android - Danang Setiawan; Harry Witriyono; Dedy Abdullah; Yulia Darmi (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2022)
Based on existing tourist statistics, the tourism sector can be the mainstay of Bengkulu Province for regional income, apart from tourism, regional income can also be obtained from other sectors which include industries such as the handicraft industry, souvenir industry, lodging, and transportation, as well as event utilization. every year. But problems often arise when tourists who do not use Travel Agent assistance, tourists must determine the destination of tourist attractions which they feel will be inconvenient because the information obtained may not necessarily solve the problem. Then made an android-based application that aims to simplify and speed up the work process and make it easier for smartphone gadget users to communicate. So that the application that is formed is truly in accordance with the needs, then an application test is carried out using the black box testing method.